Evaluation of heavy metals content in different local brands of bottled drinking water / Wan Noni Afida Ab Manan and Nurul Nadirah Zulkifli - Ab Manan, Wan Noni Afida; Zulkifli, Nurul Nadirah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
A high concentration of heavy metals in bottled drinking water has affected many people around the world in a long-term effect. This study investigates the physical and chemical properties of local brands of bottled drinking water. Thus, the aims of this study are to determine selected heavy metals concentration and to estimate health risks. Four different local brands of drinking water were purchased from the supermarket as the samples in this study. All water samples were labelled as Sample A, B, C, and D. The pH, temperature, and types of heavy metals present in the drinking water samples were identified and the Chronic Daily Intake (CDI) and Hazard Quotient (HQ) were estimated. All samples were analysed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) for determining the concentration of heavy metals. The pH for all drinking water samples was within the limits. The temperature for all samples was ranged from 23.5 to 23.9 °C. The types of heavy metals that exist in the drinking water samples were Al, Fe, and Mg with a range of metals between 0.02 - 0.09 mg/l. In conclusion, all drinking water samples are safe to consume as all water samples were HQ < 1 and within the acceptable range of metals in water.